Pengaruh Gaji, Upah Lembur, dan Bonus terhadap Produktivitas Kerja Karyawan PT BPD Kaltim Kaltara KCU Samarinda - Sudarlan, Sudarlan; Zulfikar, Zulfikar; Ain Farhanah, Nur (Jurnal EKSIS, 2024)
This study aims to determine and analyze the effect of salary, overtime pay, and bonuses on the work productivity of employees of PT BPD Kaltim Kaltara KCU Samarinda. This research uses quantitative methods. Data were collected by interview and questionnaire techniques. Respondents in this study were 80 people. The data analysis technique used is multiple linear regression with the help of IBM SPSS Statistics 20 for windows software. The results showed that partially the salary and bonus variables had a significant effect on the work productivity of employees of PT BPD Kaltim Kaltara KCU Samarinda, while the variable of overtime pay had no significant effect on the work productivity of employees of PT BPD Kaltim Kaltara KCU Samarinda, and simultaneously the variables of salary, overtime pay, and bonuses have a significant effect on the work productivity of PT BPD Kaltim Kaltara KCU Samarinda employees. Keywords: Work Productivity, Salary, Overtime Pay, Bonus.